Long-term effects of a parent-based language intervention on language outcomes and working memory for late-talking toddlers: $hAnke Buschmann, Bettina Multhauf, Marcus Hasselhorn and Joachim Pietz - Buschmann, Anke; Multhauf, Bettina; Hasselhorn, Marcus; Pietz, Joachim (Journal of early intervention, 2015)
A randomized control intervention study was conducted to evaluate the effects of the highly structured Heidelberg Parent-Based Language Intervention (HPLI). The...
Gesehen am 27.10.2020